2023
DOI: 10.1681/asn.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Is Characterized by Expansion of a Distinct Proinflammatory Intermediate Monocyte Subtype and by Increased Monocyte Adhesion to Endothelial Cells

Abstract: Significance Statement CKD is accompanied by abnormal inflammation, which contributes to progressive loss of functional renal tissue and accelerated cardiovascular disease. Although studies have documented that dysregulation of monocyte maturation and function is associated with CKD and its complications, it is not well characterized. This study reveals that a distinctive human monocyte subtype with high propensity for releasing proinflammatory mediators and activating endothelial cells is increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…As evidenced by Huang et al, a signi cant relationship between neutrophil and monocyte counts with proteinuria was found among 12,225 normal, healthy individuals who underwent hospital examinations [49]. In addition, Cormican et al discovered that only intermediate monocytes (IMs) with high human leukocyte antigen (HLA)-DR expression levels increased in individuals with CKD compared with healthy controls, indicating different monocyte subpopulations may play different roles in the process of in uencing eGFR [50].…”
Section: Discussionmentioning
confidence: 96%
“…As evidenced by Huang et al, a signi cant relationship between neutrophil and monocyte counts with proteinuria was found among 12,225 normal, healthy individuals who underwent hospital examinations [49]. In addition, Cormican et al discovered that only intermediate monocytes (IMs) with high human leukocyte antigen (HLA)-DR expression levels increased in individuals with CKD compared with healthy controls, indicating different monocyte subpopulations may play different roles in the process of in uencing eGFR [50].…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, chronic kidney disease is associated with increased numbers of HLA-DR high circulating proinflammatory intermediate monocytes, increased migration toward CCL5, and adhesion to primary endothelial cell layers 33 . In the aged mouse brain, it has been reported that parenchymal border macrophages comprise of less Lyve-1 + cells and more MHC-II + cells 11,34 .…”
Section: Discussionmentioning
confidence: 99%
“…While the MHC-II high subset receives modest monocyte contribution and is not continually replaced, the CCR2 + subset is almost entirely replaced by monocytes and is therefore more dynamic. Interestingly, chronic kidney disease is associated with increased numbers of HLA-DR high circulating pro-inflammatory intermediate monocytes, increased migration toward CCL5, and adhesion to primary endothelial cell layers 33 . In the aged mouse brain, it has been reported that parenchymal border macrophages comprise of less Lyve-1 + cells and more MHC-II + cells 11, 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory PT cells may also receive signaling from stromal cells as they expressed receptors for FAS and TWEAK (Fig. 4F), while the ligands were expressed by NK cells (FAS) and monocytes (TWEAK), with both these cell types being implicated in kidney disease (19,30). While these are classically considered pro-apoptotic factors, they can also promote in ammation via NF-κβ signaling (31,32) and hence enable bi-directional cross talk between leucocytes and in ammatory PT cells to mediate renal in ammation.…”
Section: Inter-cellular Signaling Pathways Between In Ammatory Tubule...mentioning
confidence: 99%